2017
DOI: 10.1002/jgf2.58
|View full text |Cite
|
Sign up to set email alerts
|

A periodontal disease care program for patients with type 2 diabetes: A randomized controlled trial

Abstract: BackgroundDiabetes and periodontitis are interrelated, and patient education and guidance are important. Therefore, we conducted a periodontitis care program for patients with type 2 diabetes to provide education about diabetes and periodontitis and to promote self‐care skills, and we evaluated the effectiveness of this program.MethodsThis was a randomized controlled trial. Thirty‐eight and 39 adult patients diagnosed with type 2 diabetes were allocated to the intervention and control groups, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
10
0
4
Order By: Relevance
“…A metaanalysis showed a signi cant reduction of glycated haemoglobin on T2DM patients with periodontitis after non-surgical periodontal therapy using scaling and root planing (SRP) with a minimum of 3-months follow-up. A previous study in Japan found a signi cant improvement of bleeding on probing after 4-time, every 6-8 months dental education program for oral self-care, but did not change in glycated haemoglobin among T2DM patients with periodontitis 12 . Thus, with the current evidence, professional periodontal treatment is required to improve oral health and glycemic control in diabetic patients with periodontitis, and further study needs more follow-up periods 13 .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A metaanalysis showed a signi cant reduction of glycated haemoglobin on T2DM patients with periodontitis after non-surgical periodontal therapy using scaling and root planing (SRP) with a minimum of 3-months follow-up. A previous study in Japan found a signi cant improvement of bleeding on probing after 4-time, every 6-8 months dental education program for oral self-care, but did not change in glycated haemoglobin among T2DM patients with periodontitis 12 . Thus, with the current evidence, professional periodontal treatment is required to improve oral health and glycemic control in diabetic patients with periodontitis, and further study needs more follow-up periods 13 .…”
Section: Introductionmentioning
confidence: 79%
“…However, the reduction of HbA1c level did not meet the target of American Diabetes Association treatment goal that the HbA1c level must be reduced to less than 7.5 in healthy older people 12 . In other previous studies [24][25][26][27] , periodontal therapy in diabetic patients could signi cantly reduce HbA1c levels from 0.29-0.64% in 3-month and 0.2% in 6-month after completion of the therapy 28 . As the combination of lifestyle changes and dental care program also decreased HbA1c (0.29%) after 3-months follow-ups, whereas the HbA1c increased 0.09% in the control group 19 .…”
Section: Discussionmentioning
confidence: 98%
“…Regarding oral care by nurses (29)(30)(31)(32)(33)(34), it has been pointed out that nurses lack knowledge of oral health care (35). And nurses need to know that many patients want to get knowledge about oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Three publications presented the effect of diabetes control interventions in periodontitis patients (Holmer et al, 2018;Nishihara et al, 2017;Saengtipbovorn & Taneepanichskul, 2015). The interventions mainly consisted of individual lifestyle counsellings including dietary changes and oral health education.…”
Section: Diabetes Control In Periodontitis Patientsmentioning
confidence: 99%